2023
DOI: 10.1002/fld.5169
|View full text |Cite
|
Sign up to set email alerts
|

A scalable compressible volume of fluid solver using a stratified flow model

Abstract: In this paper, a Volume of Fluid method which uses a Stratified Flow model for flux calculation is proposed to solve a compressible multiphase flow in a way that has high parallel efficiency. The solver is part of an open‐source computing tool to study fuel entrainment and combustion in the application of paraffin‐based hybrid rocket motors. This paper focuses on the compressible Volume of Fluid solver for the liquid and gaseous phases in this environment. This solver uses perfect gas and stiffened gas models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…It uses explicit solvers and a stratified flow model to improve scalability, as this allows for a multiphase solution without the reconstruction of the interface. The code is validated in multiple research papers [29,30].…”
Section: Methodology and Simulation Domainmentioning
confidence: 99%
“…It uses explicit solvers and a stratified flow model to improve scalability, as this allows for a multiphase solution without the reconstruction of the interface. The code is validated in multiple research papers [29,30].…”
Section: Methodology and Simulation Domainmentioning
confidence: 99%
“…Feng et al [5] demonstrated the two phase stratified flow in three dimensions along with thermal mixing and direct contact condensation by utilizing the CFD approach. To explore the aspects of compressible multiphase flow using a technique that has high parallel efficiency, Sementilli et al [6] considered a stratified flow model. Investigation about the MHD stratified fluid flow over a cylindrical surface incorporating Brownian motion and thermophoresis effects was made by Majeed et al [7].…”
Section: Introductionmentioning
confidence: 99%